Assessing Reading Rate in the Primary Grades (1–3). Issue 7 (3rd October 2017) - Morris, Darrell; Trathen, Woodrow; Gill, Tom; Schlagal, Robert; Ward, Devery; Frye, Elizabeth M.
Abstract : In this study we explore students' reading rates in grades 1–3. We begin with a short history of reading rate as an assessment measure in the early grades. Next, we share rate data from a recent study ( N = 305) where children's contextual reading was assessed with a traditional passage-reading inventory. A comparison of our average grade-level rates with those rates reported in the DIBELS literature shows that they match closely. Finally, we introduce the concept of minimum grade-level rates, emphasizing its practical significance to teachers and researchers alike.